Euiin-Tang Attenuates Obesity-Induced Asthma by Resolving Metaflammation - Ye-Eul Lee; Dong-Soon Im (MDPI AG, 2024)
Euiin-tang reduces obesity and hypertension. Patients with obesity may develop obesity-induced asthma (OIA) owing to phlegm dampness. This study aimed to determine whether euiin-tang alleviates high-fat diet (HFD)-induced OIA in C57BL/6 mice. OIA was developed by HFD feeding for 15 weeks in C57BL/6 mice, and euiin-tang (5 mg/10 g/day) was orally administered for the last five weeks. Oral administration of euiin-tang suppressed HFD-induced changes in body weight, liver weight, airway hypersensitivity (AHR), and immune cell infiltration in bronchoalveolar lavage fluid. Histological analysis revealed that euiin-tang treatment suppressed HFD-induced mucosal inflammation, hypersecretion, and fibrosis. The lungs and gonadal white adipose tissue showed increased expression of inflammatory cytokines (IL-1β, IL-17A, TNF-α, IL-6, IL-13, IFN-γ, MPO, and CCL2) following HFD, whereas euiin-tang inhibited this increase. HFD also increased the number of pro-inflammatory CD86+ M1 macrophages and decreased the number of anti-inflammatory CD206+ M2 macrophages in the lungs, whereas euiin-tang treatment reversed these effects. HFD induced a decrease in adiponectin and an increase in leptin, which was reversed by euiin-tang. Therefore, euiin-tang may be a potential therapeutic agent for OIA because it suppresses metaflammation as demonstrated in the present study.